2013
DOI: 10.3892/mmr.2013.1697
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between dopamine receptors and the Na+/K+-ATPase (Review)

Abstract: Abstract. Dopamine (DA) receptors, which belong to the G protein-coupled receptor family, are the target of ~50% of all modern medicinal drugs and constitute a large and diverse class of proteins whose primary function is to transduce extracellular stimuli into intracellular signals. Na + /K + -ATPase (NKA) is ubiquitous and crucial for the maintenance of intracellular ion homeostasis and excitability. Furthermore, it plays a critical role in diverse effects, including clinical cardiotonic and cardioprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Dopamine inhibition of Na + , K + -ATPase and other tubular sodium transporters was then confirmed by different experimental studies [6]. Through this mechanism, most of the hormonal factors related to sodium excretion exert their natriuretic actions [2, 14, 31, 43].…”
Section: Renal Dopamine: Function and Regulation Steps Of A Local mentioning
confidence: 95%
See 2 more Smart Citations
“…Dopamine inhibition of Na + , K + -ATPase and other tubular sodium transporters was then confirmed by different experimental studies [6]. Through this mechanism, most of the hormonal factors related to sodium excretion exert their natriuretic actions [2, 14, 31, 43].…”
Section: Renal Dopamine: Function and Regulation Steps Of A Local mentioning
confidence: 95%
“…After that, several reports clearly demonstrated that the intrarenal synthetized dopamine constitutes a peripheral dopaminergic system and that renal dopamine is a modulator of blood pressure, sodium balance, and renal functions, independently of the neural dopaminergic system [3]. The importance of dopamine as a natriuretic hormone is reflected through its capacity to inhibit the majority of renal tubule sodium transporters [2, 6]. Notably, the activity of Na + , K + -ATPase is inhibited in most of the tubular segments by dopamine, where it acts by opposing the effects of antinatriuretic factors, such as angiotensin II (ANG II) [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of certain genetic precursors and environmental impacts (epigenetics), an insufficiency of D2 receptors may affect individuals as high-risk for several addictive, impulsive, and compulsive behaviors [36]. It is well known that alcohol and other drugs of abuse, as well as most positive reinforcers (i.e., sex, food, gambling, aggressive thrills) cause activation and neuronal release of brain dopamine and involvement of the Na +/ K +− ATPase [37]. Dopamine release can decrease negative feelings and satisfy abnormal cravings for alcohol, cocaine, heroin and nicotine, which including others, are associated with reduced dopamine activity [38].…”
Section: Hypothesismentioning
confidence: 99%
“…D 1 -like receptors inhibit salt and water transport in tubular cells, relax vascular smooth muscle, and inhibit sympathetic nervous system activity [34,35]. Stimulation of D 1 -like receptors is associated with natriuresis and diuresis in states of sodium loading, without a requirement for increased renal blood flow [36,37]. During sodium depletion, the effects of D 1 -like receptor ligation are largely lost, with recent work implicating an interaction with the renin–angiotensin signaling pathway [38▪▪].…”
Section: Dopaminementioning
confidence: 99%